2020
DOI: 10.1038/s41598-020-72164-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations of procalcitonin, C-reaction protein and neutrophil-to-lymphocyte ratio with mortality in hospitalized COVID-19 patients in China

Abstract: Coronavirus disease 2019 (COVID-19) is an important and urgent threat to global health. Inflammation factors are important for COVID-19 mortality, and we aim to explore whether the baseline levels of procalcitonin (PCT), C-reaction protein (CRP) and neutrophil-to-lymphocyte ratio (NLR) are associated with an increased risk of mortality in patients with COVID-19. A retrospective study was conducted and a total of 76 patients with confirmed COVID-19 were included between January 17, 2020 to March 2, 2020, of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
91
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 29 publications
(26 reference statements)
12
91
1
9
Order By: Relevance
“…In COVID-19; age, comorbidities, lymphocytopenia, elevated alanine aminotransferase, D-dimer, creatine kinase, highsensitivity cardiac Troponin, and prothrombin time were associated with ICU admission and disease severity. In addition, older age, higher Sequential Organ Failure Assessment (SOFA) score, D-dimer, Troponin, and CRP levels at admission were associated with hospital mortality [17][18][19]. In our study, patients in intensive care were older and had more comorbidities (hypertension, diabetes mellitus, vascular disease) and higher D-Dimer, Troponin I, and CRP values.…”
Section: Discussionmentioning
confidence: 57%
“…In COVID-19; age, comorbidities, lymphocytopenia, elevated alanine aminotransferase, D-dimer, creatine kinase, highsensitivity cardiac Troponin, and prothrombin time were associated with ICU admission and disease severity. In addition, older age, higher Sequential Organ Failure Assessment (SOFA) score, D-dimer, Troponin, and CRP levels at admission were associated with hospital mortality [17][18][19]. In our study, patients in intensive care were older and had more comorbidities (hypertension, diabetes mellitus, vascular disease) and higher D-Dimer, Troponin I, and CRP values.…”
Section: Discussionmentioning
confidence: 57%
“…In the present study, elevations of body temperature and procalcitonin were limited. Similarly, Xu et al demonstrated a limited increase in procalcitonin levels and suggested that the limited increase could be associated with increased interferon-gamma levels (33). Also, Tharakan et al reported that a significant increase was observed in mortality for every 0.5 °C increase in body temperature (34).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Though the study did not attribute different features like Neutrophil -Lymphocyte Ratio or CRP / Albumin Ratio, it did look into the Hazard Ratios separately. [25] As discussed above, the model takes all the above features, reasonably congruent with the published international studies, and provides the prediction using a Gradient Boosting method. The Gradient Boosting method is a popular technique that recursively fits multiple predictors and a weak learning system with the residual to increase the model's accuracy using various iterations.…”
Section: Discussionmentioning
confidence: 90%